The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1021/ef700423g
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Isoalkanes in Waxes and Their Influence on Their Physical Properties

Abstract: The purpose of this paper is to display the influence of isoalkanes on the structure and mechanical properties of waxes. This work was carried out by means of X-ray diffraction, differential thermal analyses, and dynamic mechanical analyses. Isoalkanes coming from an industrial wax were added in different quantities to a synthetic mixture of linear alkanes. The disorder generated by this addition was estimated by X-ray diffraction; it modifies the structural transformations versus temperature and therefore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…For example, a-olefin waxes with low molecular weight are relatively soft but have desirable high melt flow, whereas high molecular weight waxes such as polyethylene waxes are extremely hard and have desirable high physical strength, but their viscosity is usually undesirably very high. The degree of crystallinity of waxes is also a significant parameter in defining their properties (Petitjean et al 2008). Scarce studies are found in the literature relating composition and chemical structure to crystallinity (Basson & Reynhardt 1992;Dorset 1997;Dirand et al 1998).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…For example, a-olefin waxes with low molecular weight are relatively soft but have desirable high melt flow, whereas high molecular weight waxes such as polyethylene waxes are extremely hard and have desirable high physical strength, but their viscosity is usually undesirably very high. The degree of crystallinity of waxes is also a significant parameter in defining their properties (Petitjean et al 2008). Scarce studies are found in the literature relating composition and chemical structure to crystallinity (Basson & Reynhardt 1992;Dorset 1997;Dirand et al 1998).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…This conclusion can also be made from the disproportional presence of alkanes of different types in the analyzed bitumen . Iso- and cycloalkanes hinder molecular motion, especially rotation along the long axis, and when these types of hydrocarbons are dominant (as in the analyzed bitumen), the s–s transition peak becomes indistinguishable . Finally, the DSC curves of macrocrystalline wax have a remarkable peculiarity: a heat flow signal between two s–s and s–l peaks never returns to the baseline .…”
Section: Resultsmentioning
confidence: 69%
“…23 Iso-and cycloalkanes hinder molecular motion, especially rotation along the long axis, and when these types of hydrocarbons are dominant (as in the analyzed bitumen), the s−s transition peak becomes indistinguishable. 34 Finally, the DSC curves of macrocrystalline wax have a remarkable peculiarity: a heat flow signal between two s−s and s−l peaks never returns to the baseline. 35 However, for bitumen, this signal crosses the baseline on both the reversing (Figure 2) and nonreversing 10 TMDSC heating curves, and here we have an indication that the "valley" between the endothermic peaks is an exotherm.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results show, among other things, an increase of the amount of amorphous phase and the number of crystallized phases with an increase of the standard deviation r. Furthermore, the analyses revealed that the amount of the amorphous phase increases with the mass of iso-alkanes added to the synthetic waxes, but the effect of the iso-alkanes is not important until 12 %, as branched alkanes in a small proportion can occupy voids or interlamellar spaces of the lattice. For higher quantities, the disorder increases sharply [45]. It seems that in real wax mixtures a formation of the amorphous phase (composed by linear and nonlinear alkanes) is very important as it promotes the formation of a single solid solution or prevents the appearance of other solid solutions [44].…”
Section: Gaussian-like Distribution Of L Europaeus Wax Alkanesmentioning
confidence: 99%